A percepção dos servidores de uma Instituição de Educação Superior (IES) sobre o assédio moral no ambiente de trabalho - Soares, Veruska Costa (2023)
Moral harassment is a degrading factor in the professional environment, consisting of the intentional repetition of gestures, words and behaviors that expose the individual or a group to humiliating and embarrassing situations, which cause very serious consequences for the health of the victims. This abusive conduct is as old as work, however discussions and academic research on this topic only expanded in the 1980s. Moral harassment is a social problem, insofar as it not only causes physical and psychological damage to the worker, but also for the institution in which he exercises his trade, considering the reduction of employee's performance and the defilement of the work environment. In this way, the theme is relevant, because the misfortunes caused by moral harassment affect the whole society, either directly or indirectly. The general objective of this research is to investigate the perception of technical-administrative staff working at the Faculty of Pharmacy, Dentistry and Nursing about moral harassment in the work environment. The research is classified as a survey, case study, exploratory and applied, with a qualitative and quantitative approach. A questionnaire applied to 60 FFOE workers is used as a data collection instrument, with closed and open questions, which were analyzed using the content analysis of Bardin (2016). The research results show that actions considered as harassment moral harassment do not tend to a high frequency on the Likert scale, however, a significant percentage of 61.7% of respondents consider that the public servant, although stable, is afraid to formalize a complaint of moral harassment.